Evaluation and optimization of a novel cascade refrigeration system driven by waste heat - Zheng, Weibo; Zhou, Hongbin; Xiao, Zhiyong; Sun, Dong; Song, Changshan; Zhang, Xiaohan; Li, Jianbo (Frontiers in Energy Research, 2023)
Direct discharge of waste heat from internal combustion engines (ICEs) is unfavorable for the efficient and clean fuel utilization. Here, a novel combined absorption-compression cascade refrigeration cycle is proposed to efficiently capture low-grade waste heat and supply cooling capacity for food freezing in vessels or refrigerated trucks. The intention of this work lies in: i) Comprehensively evaluating the performances of the proposed system; ii) Gaining the optimal operating conditions of the system. Aimed that, analysis models of energy, exergy, economy, and environment are set up to evaluate the sweeping performances. Further, multi-objective optimization is introduced to obtain the optimal operating parameters including evaporation and condensation temperature of the low-temperature stage, generation temperature and condensation temperature of the high-temperature stage, and cascade temperature differences. By applying multi-objective optimization, the coefficient of performance and exergy efficiency of the system are elevated from 1.283 to 1.547, and 0.222 to 0.246, respectively, the discharge amount of carbon dioxide are reduced from 71.40 to 59.57 tons year−1, and annual total cost are decreased from 16,028 to 15,055 $ year−1 compared to initial operating conditions.